Boating magazine's ulimate guide to sportfishing tips,tricks,and tactics for the serious angler - Rudow, Lenny (McGraw Hill, 1998)
Aims to help you sharpen your hooks and your skills as an angler. This title gives them the expert's lowdown on stalking their elusive prey.